The Research on Huizhou Traditional Dwellings in China from the Perspective of Green Architecture - Juan , Chen; Pintong, Sarawuth (Journal of Roi Kaensarn Academi, 2024)
Huizhou traditional dwellings occupy an important position in the history of Chinese architecture with their unique architecture style and cultural connotation. From the perspective of green architecture, this article explores the practice and wisdom of Huizhou traditional architecture in terms of ecological adaptability, resource conservation, and sustainable development. Firstly, the article introduces the theoretical basis of Chinese traditional architecture and explores its importance in sustainable development and environmental protection. Next, the traditional residential architecture of Huizhou is analyzed, including the Impact factors, the characteristics of the architecture types, and the Green wisdom embedded in them. To study the green architecture wisdom of Huizhou traditional dwellings, the researcher must not only focus on the architectures themselves but some relevant contexts around the research objectives must also be taken into account. This is because factors such as geographic environment, cultural heritage, and construction technology together shape the unique appearance of Huizhou traditional dwellings. After comprehensive analyses, it is concluded that Huizhou dwellings have achieved good natural ventilation, lighting, and water management through rational site selection, layout, material selection, and architectural structure design, reflecting the core concepts of green architecture. These traditional wisdom not only play an important role in traditional architecture but also have important reference significance for modern green architecture design.